Airbnb’s Path to Sustainability: Navigating Profit, Purpose, and Public Accountability in the Sharing Economy - Cotrim, J. (SAGE Publications: SAGE Business Cases Originals, 2026)
Airbnb’s rise as a leader in the Sharing Economy (SE) highlights the tensions between rapid platform growth, sustainability, and public accountability. Initially celebrated as a disruptor in the hospitality industry, Airbnb now faces growing scrutiny over its impact on housing markets, labor rights, and environmental sustainability. Amid increasing regulatory constraints and shifting consumer expectations, Airbnb’s leadership must decide: Can Airbnb position sustainability as a competitive advantage, or will increasing regulatory and stakeholder pressures force it to compromise financial growth? This case study places students in the role of strategic business consultants, challenging them to analyze Airbnb’s sustainability strategies, stakeholder conflicts, and regulatory responses. Using Goal-Framing Theory and Conscious Capitalism principles, students will evaluate whether Airbnb should prioritize long-term sustainability efforts at the potential expense of short-term financial gains, or adopt a profit-driven approach with minimal sustainability commitments.